Social Media, Word of Mouth, Trust: Impact on Consumer Satisfaction: Dampak Pemasaran Media Sosial, Word of Mouth, dan Kepercayaan pada Kepuasan Konsumen - Dalila Ali Al Chotib; Lilik Indayani (Universitas Muhammadiyah Sidoarjo, 2022)
This research investigates the impact of social media marketing, word of mouth, and trust on consumer satisfaction at a selected branch of Terang Bulan TOP, Sidoarjo. The study aims to address the decline in sales despite the proper implementation of social media marketing and word of mouth strategies. A quantitative approach was adopted, and data was collected through questionnaires distributed to 100 customers who had made at least two purchases at the branch. The data analysis involved multiple linear regression using SPSS version 18. The findings indicate that social media marketing, word of mouth, and trust significantly influence consumer satisfaction. Moreover, the variables collectively exert a significant influence on consumer satisfaction. The implications of this study highlight the importance of optimizing social media marketing, fostering positive word of mouth, and cultivating trust to enhance consumer satisfaction in the context of Terang Bulan TOP, Sekardangan Branch, Sidoarjo. Highlights: Effective marketing strategies: Examining the impact of social media marketing and word of mouth on consumer satisfaction. Trust and satisfaction: Investigating the role of trust in shaping consumer satisfaction in the context of Terang Bulan TOP, Sidoarjo. Holistic approach: Highlighting the simultaneous influence of social media marketing, word of mouth, and trust on consumer satisfaction. Keywords: Social media marketing, Word of mouth, Trust, Consumer satisfaction, Quantitative study.